Fixed voice telephony in economies of different sizes: When industry policy meets technological change - Symeou, Pavlos C.; Pollitt, Michael G. (My University, 2014)
The diffusion of fixed voice telephony has traditionally been backed by regulatory policies advocating industrial change, private involvement, and industry supervision. In the light of great ambiguity in the outcomes of such measures, this paper calls for consideration of the effect of technological change reflected in mobile telephony diffusion and the moderating role of economy size that depicts market and economic conditions. Based on an econometric analysis of data for 168 economies for the period 1980-2008, the research findings indicate that existing studies have overvalued the effects of industry policy measures on fixed voice diffusion. Technological change challenges policy's role as it shows a much more consistent leverage for fixed voice diffusion. The relationship between the two communication technologies and the outcomes of certain industry policies are moderated by economy size.
Keywords: Economy size; Fixed voice telephony; Industry policy; Mobile telephony; Technological change